Acute alcoholic hepatitis as indication for liver transplantation. Issue 2 (April 2016) - Jesudian, Arun B.; Brown, Robert S.
Abstract : Purpose of review: Until recently, severe acute alcoholic hepatitis that is refractory to medical therapy was a disease with extremely high mortality and no viable treatment options. A landmark trial of early liver transplantation in highly selected patients demonstrated a clear survival benefit and favorable posttransplant outcomes. Since then, new findings regarding medical therapy for alcoholic hepatitis, outcomes of early transplant, and ethical considerations as well as public perception of this intervention have been published. Recent findings: Glucocorticoids remain the best initial medical therapy for severe acute alcoholic hepatitis, but liver transplantation can be an acceptable and effective therapy for those who fail to respond to steroids. Recurrence of harmful drinking is a valid concern, and has been observed in long-term follow-up of patients transplanted for alcoholic liver disease. Public perception of early liver transplant for severe acute alcoholic hepatitis is overall positive. Summary: Liver transplantation for refractory severe acute alcoholic hepatitis is a life-saving intervention and should be judiciously employed in highly selected individuals who are at low risk of recidivism.